Do Psychology and Non-Psychology Students Differ in Test Anxiety? - Novendawati Wahyu Sitasari; Marhisar Simatupang; Law Mei-Yui; Zariv Chew Long Kwan; Mikaela Berliyana Alitani (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Test anxiety is a major concern in higher education due to its negative impact on students’ academic performance and psychological well-being. However, comparative studies across academic disciplines in the Indonesian context remain limited. This study aimed to examine differences in test anxiety between Psychology and Non-Psychology students. A quantitative comparative design was employed, involving 280 undergraduate students (140 Psychology and 140 Non-Psychology) selected through convenience sampling. Test anxiety was measured using a scale adapted from Brooks et al. (2015), which demonstrated high reliability (α = .92). Data were analyzed using an Independent Samples t-Test. The results showed that Levene’s test indicated unequal variances (F = 15.463, p < .05); therefore, the unequal-variance assumption was applied when interpreting the t-test results. A significant difference in test anxiety was found between groups (t = 4.651, p < .001), with Psychology students reporting higher anxiety levels (M = 209.69) than Non-Psychology students (M = 198.34). The effect size was moderate (Cohen’s d = .56). These findings highlight the importance of discipline-sensitive assessment practices and targeted psychological interventions, particularly for Psychology students. Keywords: academic discipline, psychology students, test anxiety